Incidence of Occupational Asthma and Exposure to Toluene Diisocyanate in the United States Toluene Diisocyanate Production Industry. (December 2017) - Collins, James J.; Anteau, Steve; Conner, Patrick R.; Cassidy, Laura D.; Doney, Brent; Wang, Mei Lin; Kurth, Laura; Carson, Michael; Molenaar, Don; Redlich, Carrie A.; Storey, Eileen
Abstract : Objective: This study examines asthma risk in facilities producing toluene diisocyanate (TDI). Methods: A total of 197 workers were monitored from 2007 to 2012. TDI air concentrations were used to estimate exposures. Results: The incidence of cases consistent with TDI-induced asthma was 0.009 per person-years (seven cases) or consistent with TDI-induced asthma or asthma indeterminate regarding work-relatedness was 0.012 (nine cases). Increased risk of cases consistent with TDI asthma was observed for cumulative (odds ratio [OR] = 2.08, 95% confidence interval [CI] 1.07 to 4.05) per logarithm parts per billion-years and peak TDI exposures (OR = 1.18, 95% CI 1.06 to 1.32) (logarithm parts per billion). There was a weak association with cumulative and peak exposures for decline of short-term forced expiratory volume in one second (FEV1 ). Asthma symptoms were associated with workers noticing an odor of TDI (OR 6.02; 95% CI 1.36 to 26.68). Conclusions: There is evidence that cumulative and peak exposures are associated with TDI-induced asthma.